Synergistic regulation of DACH1 stability by acetylation and deubiquitination promotes colorectal cancer progression - Liang Zhu; Can Cheng; Heng Li; Jingwen Liu; Yang Wu; Liang Wu; Hanhui Yao (Cell Death and Disease)
Abstract Colorectal cancer (CRC) remains a significant challenge in oncology, with limited therapeutic options for aggressive subtypes. This study elucidates the critical roles of USP7 and DACH1 in CRC, revealing their involvement in tumor progression and potential as therapeutic targets. USP7 was identified as a deubiquitinase that stabilizes DACH1, enhancing its tumor-promoting activities. Mechanistically, USP7 directly interacts with DACH1, protecting DACH1 from UHRF1-induced ubiquitination and degradation by removing ubiquitin chains, particularly K48-linked types, which are crucial for protein degradation. Additionally, acetylation at K680 on DACH1, mediated by acetyltransferase GCN5, enhances its interaction with USP7, further influencing DACH1 stability and function. Clinically, high levels of USP7 and DACH1 correlate with poor prognosis in CRC patients, underscoring their significance in disease progression. These findings suggest that targeting the USP7-DACH1 axis could offer a novel therapeutic strategy for managing CRC, particularly in forms characterized by aggressive and metastatic behaviors.